(untitled) (Bangladesh Journal of Zoology, 2019)
The cottony cushion scale, Icerya purchasi, one of the devastating pests of citrus and ornamentals distributed all over the world. A study was conducted on the biology, abundance and mechanical control of this pest on mango plants from at two locations of Dhaka, Bangladesh. Simple linear regression lines were produced on the lengths and widths of different nymphal instars and adult of this pest. It was proved that body lengths and widths were highly correlated with the successive changing of the nymphal instars from 1st, 2nd and 3rd to adults. The maximum abundance of the I. purchasi on mango leaves was 310 ± 21 in March, 2016. The results of the mechanical control method by hand crushing showed that it was highly effective to control this insect. Abundances of this insect before and after treatment were significantly different (p < 0.05). Abundances of insects in different sampling times were showed different by Tukey’s HSD test (p < 0.05). Bangladesh J. Zool. 47(1): 89-96, 2019